lmplementasi Sistem Informasi Manajemen Dalam Pemasaran Usaha Mikro Kecil Menengah - Hayati, Ridha Nurul; Husain, Husain; Ardiansyah, Lalu Yayan (Income : Digital Business Journal, 2024)
The number of entrepreneurs in Indonesia is less than 0.24 percent of Indonesia's population of around 238 million people. Therefore, according to the Minister of Cooperatives and Small and Medium Enterprises, Syarifuddin Hasan, the number of entrepreneurs still needs to be increased in order to support economic growth in Indonesia. Bumigora University as one of the private universities in Indonesia is very aware of the importance of entrepreneurship. Since 2019, Bumigora University has made Management Information Systems a course. This research method is descriptive qualitative which aims to implement experienced phenomena, such as behavior, perception, motivation, etc., comprehensively and descriptively in the form of words and language, in context. certain realms at certain times and using different realms. Based on the results of research conducted at UD. Angel Telur which is on JL. Adisucito, Ampenan, Mataram City: The implementation of this SIM is applied to UD MSMEs. Angel Telur, after implementing the SIM, UD. Angel Telur experienced an increase in the number of sales and customers who came, as for the components in UD MSMEs. Angel Egg is (1) social media IG, Facebook, (2) Google Maps, (3) Banner, (4) WhatsApp, (5) Website, (6) Online Courier Collaboration